A Personal Tribute to Bob Jahn - Bengston, William (Journal of Scientific Exploration, 2018)
Bob Jahn was the only person I ever met who spoke in complete, edited sentences. No, it was more than that; I think there were embedded paragraph structures when he spoke. A transcription of any of his talks would have the unsuspecting reader think that multiple iterations of his thoughts on paper had finally yielded the most parsimonious edited version of an intellectual tour de force. And after the pleasure of hearing him speak, it was not possible to read any of his voluminous written output without hearing the cadence and tone of his voice. Bob was not an ordinary guy. His biography is well known to us, from his lofty academic perch to his founding of the PEAR lab, to his central role in the founding of the SSE and becoming its longest serving officer; to to to… There is little I could contribute that hasn’t been adequately covered elsewhere. Instead, I want to make this a more personal expression of gratitude. I first met Bob in person the same way many of you likely did; at an SSE conference. My first SSE was at the Albuquerque conference in 1999, where I gave my debut public talk on some anomalous healing data. As a newbie to the SSE I was a bit star struck by some of the luminaries I had only previous read from afar. Of course I had read Margins of Reality, but actually sitting behind Bob Jahn and Brenda Dunne in the flesh made me a bit wide eyed. And that’s not to mention seeing and hearing Peter Sturrock, the SSE president and founder, Larry Dossey, Hal Puthoff, Jacques Benveniste, John Mack, and so many others. The place was like a who’s who among anomalies researchers. How would these folks take to my presentation?